Targeting Protein Prenylation in Progeria - Young, Stephen G. (2013)
A clinical trial of a protein farnesyltransferase inhibitor (lonafarnib) for the treatment of Hutchinson-Gilford progeria syndrome (HGPS) was recently completed. Here, we discuss the mutation that causes HGPS, the rationale for inhibiting protein farnesyltransferase, the potential limitations of this therapeutic approach, and new potential strategies for treating the disease.